Gross science projects - Halls, Kelly Milner, 1957- (Project: STEAM., 2019)
Presents a collection of activities that engage young readers in using science to produce smelly, creepy and icky creations. Includes step-by-step instructions, color photographs, text-related questions, a glossary, and resources for further information.